2016
DOI: 10.1038/srep31916
|View full text |Cite
|
Sign up to set email alerts
|

Human Ex-Vivo Liver Model for Acetaminophen-induced Liver Damage

Abstract: Reliable test systems to identify hepatotoxicity are essential to predict unexpected drug-related liver injury. Here we present a human ex-vivo liver model to investigate acetaminophen-induced liver injury. Human liver tissue was perfused over a 30 hour period with hourly sampling from the perfusate for measurement of general metabolism and clinical parameters. Liver function was assessed by clearance of indocyanine green (ICG) at 4, 20 and 28 hours. Six pieces of untreated human liver specimen maintained stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…The use of APAP toxicity in this platform gives information on cell disruption and necrosis in the hydrogel similar to what ex vivo human models have shown. 39 Additionally, the HUVEC layer is also shown to be disrupted, making this a suitable system for drug testing and assessment of cell death within the hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…The use of APAP toxicity in this platform gives information on cell disruption and necrosis in the hydrogel similar to what ex vivo human models have shown. 39 Additionally, the HUVEC layer is also shown to be disrupted, making this a suitable system for drug testing and assessment of cell death within the hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…Since the main objective of this study was to provide a deep understanding of the mechanical response of the fresh human capsule under the axial and transversal tensile and compressive loadings, only the simple mechanical approach was employed. In addition to that, other indirect injuries, as a result of the Acetaminophen, have also been investigated upon among the human liver samples [31]. Their results revealed a strong damage on low-dose acetaminophen usage.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 In addition, previous reports in vitro and ex vivo demonstrated that APAP elicits toxicity at 5-20 mM dependent on the system. [54][55][56] Therefore, we investigated the concentration range of 0.5-8 mM and chose 4 and 8 mM for further analysis based on cell viability results in our system. Exposure of HepaRG to 4 and 8 mM APAP elicited the expected hepatocellular damage in 3D culture conditions.…”
Section: Characterization Of the In Vitro Model And Determination Of mentioning
confidence: 99%